1975
DOI: 10.1073/pnas.72.4.1584
|View full text |Cite
|
Sign up to set email alerts
|

Induction of growth in resting fibroblastic cell cultures by Ca++.

Abstract: Of all the components of the culture medium, only CaCl2 induces DNA replication when added to resting cultures of Balb/c 3T3 cells. The effect is present even in a serum-free medium. Increasing the Ca++ concentration above the standard 1.8 mM in the medium of a new culture increases the total number of cells ultimately produced, without affecting the initial cell growth rate. This effect is synergistic with that of serum. The elevated Ca++ concentration also induces striking morphological changes. The Ca++ eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
1

Year Published

1976
1976
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(52 citation statements)
references
References 17 publications
(13 reference statements)
5
42
1
Order By: Relevance
“…The effect of increased calcium concentrations in the medium on 3H-TdR incorporation substantially confirm the findings of Dulbecco and Elkington (1). Simialar experiments have been carried out with the addition of other divalent cations (zinc, nickel, magnesium, manganese) to the medium but no stimulation of thymidine incorporation similar to that observed in the presence of additional calcium were found (Damluji and Riley, unpubl.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The effect of increased calcium concentrations in the medium on 3H-TdR incorporation substantially confirm the findings of Dulbecco and Elkington (1). Simialar experiments have been carried out with the addition of other divalent cations (zinc, nickel, magnesium, manganese) to the medium but no stimulation of thymidine incorporation similar to that observed in the presence of additional calcium were found (Damluji and Riley, unpubl.…”
Section: Discussionsupporting
confidence: 74%
“…Several authors (1)(2)(3) have reported that the serum-induced proliferation of quiescent 3T3 cells is characterised by alterations in the amount of calcium associated with the cells suggesting that serum stimulation of growth may be mediated in part through changes in the concentrations or localization of calcium. In this communication we demonstrate a phase in the initiation of cell proliferation during which the cells are sensitive to external calcium levels which implies that cell-associated calcium acts as a cofactor in the effect of serum.…”
Section: Introductionmentioning
confidence: 99%
“…Since extracellular calcium affects cell growth (Dulbecco and Elkington, 1975;Hazelton et al, 1979;Paul and Ristow, 1979;Nicholson et al, 1984;Kulesz-Mar-…”
Section: Calcium Does Not Alter Ceres-18 Binding Characteristics and mentioning
confidence: 99%
“…Since growth is usually required for division, the cells of many organisms, including prokaryotic (4) and eukaryotic (5-9) microorganisms, metazoa (10)(11)(12)(13)(14)(15)(16)(17), and metaphyta (18), control division in response to inorganic and organic nutrients. Some evidence exists to suggest that even the protein growth factors of mammalian cells such as serum factors and agglutinins may act by enhancing the availability of small molecular weight nutrients (19,20).…”
mentioning
confidence: 99%